Development of a measurement setup to detect the level of physical activity and social distancing of ageing people in a social garden during COVID-19 pandemic. (November 2021) - Casaccia, Sara; Naccarelli, Riccardo; Moccia, Sara; Migliorelli, Lucia; Frontoni, Emanuele; Revel, Gian Marco
Highlights: Social distancing of ageing people is measured using non-invasive and wearable sensors in a social garden scenario. The measurement setup is based on real-time location system (RTLS) with embedded inertial measurement unit (IMU) sensors. Social distancing time is measured to prevent contagion risk. The impact of measurement uncertainty in contagion risk is assessed. An uncertainty-based thresholding method for the classification of activity level on ageing people is proposed. Abstract: This study defines a methodology to measure physical activity (PA) in ageing people working in a social garden while maintaining social distancing (SD) during COVID-19 pandemic. A real-time location system (RTLS) with embedded inertial measurement unit (IMU) sensors is used for measuring PA and SD. The position of each person is tracked to assess their SD, finding that the RTLS/IMU can measure the time in which interpersonal distance is not kept with a maximum uncertainty of 1.54 min, which compared to the 15-min. limit suggested to reduce risk of transmission at less than 1.5 m, proves the feasibility of the measurement. The data collected by the accelerometers of the IMU sensors are filtered using discrete wavelet transform and used to measure the PA in ageing people with an uncertainty-based thresholding method. PA and SD time measurements were demonstrated exploiting the experimental test in a pilot case with real users.